Studi Pemikiran Imam Al-Ghazali Tentang Ekonomi Islam - Ayub Rangkuti; Febria Lasmita Sari; Fradini Brillyandra; Iren Despileny; Trian Zulhadi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
This research was conducted to determine the problems of Islamic economics during the time of Imam al-Ghazali. This research uses the library study method, a scientific activity carried out in order to collect information and data through a number of books, magazines and historical stories. Abu Hamid Muhammad bin Muhammad Al-Tusi Al-Ghazali was a Sufism expert from Iran who was very enthusiastic about all sciences. Imam Al-Ghazali has published approximately 300 books in various book fields. One of the books on economics is Ihya' Ulum al-Din. The aspects that are the object of Al-Ghazali Al-Ghazali's economic study include market exchange and evolution, production, bartering and the evolution of money, as well as the role of the State and political finance. While the starting point From Al-Ghazali's economic thoughts is the concept of Maslahah, namely a concept that covers all human activities and creates a close link between individuals and society